Performance Measurement System in complex environment: observed and unobserved risk factors - Zaki, Rezgar (UiT Norges arktiske universitet, 2020)
World demand for energy leads industry to harvest energy in complex environment with harsh conditions and sensitive areas, such as the Arctic region – one of the last remaining wild places in the world – with potentially harmful consequences. Moreover, over the past few decades, the increasing trend of melting sea ice in the Arctic has provided increased access and has created new opportunities for economic development within metals and minerals, fisheries, cargo shipping, cruising, subsea telecom cables and pipelines. However, development of the Arctic resources is assumed to be technologically and economically challenging and risky. Studies reveal that, due to low temperatures, sea ice, polar low pressures, poor visibility, seasonal darkness limitations to the logistics of supplies, etc., Arctic operational conditions have significant effects on the performance of components and industry activities in various ways, including increasing failure rate and repair time, and can cause different types of production losses. The optimal functioning of technical systems involved in design and operation in the Arctic faces numerous challenges, in order to succeed in a globally competitive market with limited resources. The concept of the Performance Measurement System (PMS) is frequently used by industries and has been shown to be an essential concept for improving efficiency and effectiveness and supporting the design, planning, and managing of a company; PMS refers to output results obtained from a system that permits evaluation and comparison, relative to past results or other companies. PMS needs up-to-date and accurate performance information on its business. This performance information needs to be integrated, dynamic and accessible, to assist fast decision-making. However, performance terminologies and standards for the Arctic reveal that the Performance Indicators (PIs) measured by industries though important, are not enough and could still be improved by identifying more important indicators, which contribute to ...